2020
DOI: 10.20944/preprints202009.0242.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and Prognosis of COVID-19 in Patients with COPD

Abstract: Patients with COPD have a higher prevalence of coronary ischemia and other factors that put them at risk for COVID-19-related complications. We aimed to explore the impact of COVID-19 in a large population-based sample of patients with COPD in Castilla-La Mancha, Spain. We analyzed clinical data in electronic health records from January 1st to May 10th, 2020 by using Natural Language Processing through the SAVANA Manager® clinical platform. Out of 31,633 COPD patients, 793 had a diagnosis of COVID-19. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
0
18
0
2
Order By: Relevance
“…Several studies approved high age as a risk factor for COVID-19 related mortality [25,26]. Graziani et al demonstrated that patients with COPD and COVID-19 (with the mean age of 75) had significantly higher risk or mortality than their non-COPD participants with the mean age of 66 [27]. National Guideline for COVID-19 issued by Scientific Advisory Board on Coronavirus affiliated with the Turkish Health Ministry recommended to hospitalize and monitor patients with COVID-19 aged above 50 years, owing to a high risk of severe disease and complications such as mortality [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies approved high age as a risk factor for COVID-19 related mortality [25,26]. Graziani et al demonstrated that patients with COPD and COVID-19 (with the mean age of 75) had significantly higher risk or mortality than their non-COPD participants with the mean age of 66 [27]. National Guideline for COVID-19 issued by Scientific Advisory Board on Coronavirus affiliated with the Turkish Health Ministry recommended to hospitalize and monitor patients with COVID-19 aged above 50 years, owing to a high risk of severe disease and complications such as mortality [8].…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients have both an increased risk of COVID-19 disease, and a poorer prognosis, with higher rates of hospitalization and mortality. (22) COPD is an independent predictor of mortality in patients admitted to ICU for COVID-19 pneumonia. (4) Diabetes Mellitus is associated with mortality in our results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a significant number of existing corpora, datasets and resources available in English. Yet, we observe an increasing number of publications dedicated to other languages and a greater variety of languages: Arabic [ 20 ], Chinese [ 21 22 23 24 25 26 ], Croatian [ 27 ], Finnish [ 28 , 29 ], French [ 30 , 31 ], German [ 32 33 34 ], Hebrew [ 35 ], Italian [ 36 37 38 ], Japanese [ 39 , 40 ], Korean [ 41 , 42 ], Norwegian [ 43 ], Portuguese [ 44 ], Spanish [ 45 46 47 48 ], Swedish [ 49 ], and Turkish [ 28 ]. Overall, we believe that the trend observed in previous years is continuing.…”
Section: Current Trends In Biomedical Nlpmentioning
confidence: 99%
“…In order to help such work, several papers present COVID-19 resources, such as the COVID-19 Open Research Dataset (CORD-19) produced by Wang et al [ 50 ] and available through the Kaggle 6 platform. Besides, several works are anchored in hospitals and propose to predict conditions and events related to COVID, such as prediction of admission of patients with COVID in an intensive care unit [ 51 ], detection of COVID cases from radiological text reports [ 46 ], prognosis prediction for patients with chronic obstructive pulmonary disease [ 45 ] or for patients with hypertension [ 31 ].…”
Section: Current Trends In Biomedical Nlpmentioning
confidence: 99%